Character Design in Games Analysis of Character Design Theory - Hagung Kuntjara; Betha Almanfaluthi (Bina Nusantara University, 2017)
A character plays an important role in game sales on an application store. The first thing people notice when choosing a certain genre of a game on the application store is the character. Character appears in a game visual icon, alongside the name of the game and some stars representing the rating and the number of download. By looking at the game character, people will be able to tell the game genre and type, also the targeted users. Advanced technology might allow a game to develop better but analyzing the game character from its art and design aspect is also needed for it to be successful in the market. This paper will explain character design development and its art and design aspect using constructive method. The analysis can be used for better understanding on how games designers work and come up with the right idea of a gameâ€™s characters based on the gameâ€™s general idea.Â